Selection of Liquid Membrane Component for Lignosulfonate Removal from Liquid Waste Solution using Emulsion Liquid Membrane Process - Othman, N.; Ooi, Z. Y.; Harruddin, N. (Journal of Applied Membrane Science & Technology, 2017)
Removal of lignosulfonate from pulping process as an external biofuel and in specialty chemicals is growing such as in production of vanillin, animal feed pellets binder, pesticides, ect. Though lignosulfonate(LS) is nontoxic, it imparts brownish black colour to the water bodies and makes them unsuitable for usage in other processes. Therefore the removal and recovery of LS is needed. This study examined the liquid membrane component selection of lignosulfonate(LS) removal from liquid waste solution using trioctylamine (TOA) as a mobile carrier in batch process using mixer settler. Several parameters have been investigated such as choice of diluents, effect of pH, concentration of carrier, concentration of LS solution, organic to aqueous treat ratio, choice of stripping agent and concentration of stripping agent. The results show that at favorable condition of 0.1M concentration of TOA in kerosene, pH 3 of solution, treat ratio 1:15 and 0.7 M NaOH solution as stripping agent showed that almost 90 percent of lignin was extracted and recovered in receiving phase.